Surgical pathology of early stage non-small cell lung carcinoma - Beasley, Mary Beth (Ann Transl Med, 2016)
The histologic classification of non-small cell lung carcinoma (NSCLC), particularly adenocarcinoma (ADC), has undergone extensive study in recent decades, ultimately resulting in an extensively updated classification system. The 2015 World Health Organization (WHO) classification of ADC provides greatly improved prognostic information in comparison to the 2004 WHO classification. Several issues still require further investigation: lepidic predominant ADC, prognostic significance of poor prognostic subtypes such as micropapillary carcinoma, the more recently described concept of spread of tumor through airspaces (STAS), and the utility of sublobar resections. While limited resection appears to be suitable for tumors with a ground glass radiographic appearance, which typically correspond to adenocarcinoma in situ (MIS) or minimally invasive adenocarcinoma (MIA) histologically, the role of sublobar resection in radiographic solid tumors is not as clear, and the impact of histologic subtypes with a poor prognosis needs further evaluation. Squamous cell carcinoma (SCC) has not been as extensively studied and the current classification lacks subclassification with significant prognostic information.